Economic Utopia. A Genealogical Study of Gary Becker’s Neoliberalism in Connection with Jeremy Bentham’s Thought (Nóema, 2016)
The aim of this work is to describe the genealogy of the neoliberal thinking, starting from the texts of Gary Becker. In this way the neoliberal economics thought is explained in the light of scientific revolution and mathematization of nature, from which it descends. Such path will lead to Jeremy Bentham, whose philosophical system is often considered as forerunner of neoliberal position. According to the thesis of the author, neoliberal economists feature theri sight as a neutral and scientific description of reality, despite of its normative vocation. This is how they map out a construction which is also prescriptive, propounding a political model; such a model is here named «economic utopia».
Keywords: Gary Becker; Jeremy Bentham; neoliberalism; utilitarianism; genealogy; economics; calculus; efficiency; homo oeconomicus